Stanislav Voronin’s Universal Classification of Onomatopoeic Words: a Critical Approach (Part 1) - M. A. Flaksman (Дискурс, 2020)
Introduction. The universal classification of onomatopoeic words was first introduced in 1969 by Stanislav V. Voronin. In the course of the following fifty years it has been tested on the material of typologically different languages both by the author himself and by other researchers. The aim of this article is to provide a full description of the classification (which has never been published in English before) and to examine its key points critically. The bulk of empirical data collected in the recent years calls for yet another update on the classification. There is a logical contradiction between such classes of onomatopoeic words as frequentatives and frequentatives-(quasi)-instants-continuants. They overlap typologically. This and other minor issues are solved in the present paper.Methodology and sources. The method discussed and applied in the classification is the method of phonosemantic analysis introduced by S. V. Voronin. Empirical data from English and other relevant languages are used for supporting the proposed changes into the classification.Results and discussion. The critical analysis of the Voronin’s universal classification of the onomatopoeic words revealed the presence of overlapping classes and hyperclasses within it, as well as other minor inconsistencies. The empirical typological data allowed to introduce some minor corrections while retaining the main principles of the classification.Conclusion. Introduced half a century ago, Stanislav Voronin’s classification of onomatopoeic words still remains a useful tool of typological research. Critical additions and proposed changes do not lessen its impact on studies in linguistic iconicity. The first part of this paper is devoted to the description of the classification and to the discussion of its advantages and limitations. In the second part of the article some possible solutions to the detected problems are suggested.